TRANSFORMATION OF ISLAMIC RELIGIOUS EDUCATION: AN ANALYSIS OF THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN CLASS VII SMPN 3 PAMEKASAN - Ach. Sayyi; Abdul Gaffar; Shofiyatun Nisak (Molang: Journal Of Islamic Education, 2023)
This research describes the implementation of an independent curriculum at SMPN 3 Pamekasan, with special emphasis on Islamic religious education subjects. The main objective of this research is to describe and understand how the independent curriculum is implemented in the context of Islamic religious education. This research uses a qualitative approach with case study as the main method. Data were collected through various techniques, including observation, interviews, and documentation, from multiple sources such as the principal, vice principal for curriculum, teachers, and students. Data were analysed using an interactive model and validated using various techniques. The results show that implementing the self-directed curriculum involves extracurricular Pancasila learner profile-strengthening projects and extracurricular. The self-contained curriculum provides flexible, creative, and meaningful learning experiences and maintains the Pancasila learner profile. It also provides opportunities for students to develop their academic and non-academic potential. This research offers new insights into how a self-contained curriculum can be implemented in Islamic religious education and how it can positively impact students, teachers, and schools. However, it also shows that successful implementation requires support, commitment, and further research.